Research on Forestry Survey and Data Acquisition System Based on Artificial Intelligence - Xia Chen (The International Journal of Multiphysics, 2024)
With the rapid development of science and technology, the application of artificial intelligence in forestry is becoming more extensive and in-depth, ushering in a digital era for forestry development. Forestry survey technology and data collection systems are essential means to achieve digital forestry. Based on the study of existing forestry survey 3S technology and data collection systems at home and abroad, this paper proposes a method based on artificial intelligence. By using a tree positioning calibration module, a plane coordinate system is established to facilitate the rapid determination of the central survey location of the forest area, and to statistically analyze the tree information at the survey points.